(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The article is about the directions of using springs in Gallaorol district of Jizzakh region and their protection from anthropogenic factors. It was found that 11 springs are neglected, 67 springs are used by the population as a source of drinking water, 16 springs are in the center of special attention as holy destinations, and 19 springs are used as recreation and sanatoriums.